Rejuvenating the failing heart: multidimensional insights into young blood-mediated anti-aging pathways - Chen, Ming-Tai; Wang, Rao-Qiong; Qian, Yu-Mei; Peng, Ting; Lan, Xiao-Yu; Liang, Ling-Ling; Luo, Gang; Liu, Qiu-Yu; Liu, Meng-Nan (Frontiers in Endocrinology, 2025)
Heart failure (HF), a serious stage of many cardiovascular illnesses associated with high morbidity and mortality, has emerged a major global public health concern worldwide. Its key pathophysiological mechanisms include cardiac remodeling, neurohormonal dysregulation and cardiac dysfunction. Despite established clinical treatments, adverse reactions and limited efficacy remain problems. In recent years, great emphasis has been paid to young blood, which is defined as blood from young people or in a youth associated physiological condition, and is abundant in various components that help maintain a youthful state of the organism. Currently, some progress has been made in the study of the anti-aging effects and mechanisms of young blood in older individuals, indicating therapeutic potential in the treatment of age-related diseases. In this paper, the major pathophysiological mechanisms of HF, the rejuvenating circulating factors in young blood and their positive effects on aging tissues are summarized. Moreover, the rejuvenating effects of young blood on the failing heart and the possible mechanisms of its action from multiple perspectives are investigated and discussed, aiming to provide theoretical foundation and potential therapeutic targets for the treatment of HF related diseases.